MENINGKATKAN KEAKTIFAN SISWA MELALUI PENERAPAN QUIZIZZ DALAM PEMBELAJARAN BIOLOGI - Bule, Margareta Vilkanova Muwa; Kea, Alfian Sabina; Daud, Maimunah H; Sade, Maria Patrisia (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The application of Quizizz at SMA Negeri 2 Ende, as part of the teaching assistance program, aims to increase student activity and involvement in the learning process. Based on the results of observations, it was found that the use of technology, especially Quizizz, can create an interactive and fun learning atmosphere. The implementation method is carried out through several stages, including observation, making teaching modules, and implementing quizzes. The results showed increased student participation and better understanding of the material. Although there are challenges such as limited access to technology, the benefits obtained are very significant. To increase the effectiveness of Quizizz implementation, it is recommended that schools ensure adequate access to technology, provide continuous training for teachers, and conduct regular evaluations. With these steps, it is expected that the implementation of Quizizz will continue to offer optimal benefits in improving the quality of education at SMA Negeri 2 Ende.